Nanoindentation approach on investigating micromechanical properties of joining from green solder materials - Maria Abu Bakar,; Azman Jalar,; Abdul Razak Daud,; Roslina Ismail,; Nur Azida Che Lah,; Najib Saedi Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This work investigates the micromechanical properties of Sn96.5Ag3.0Cu (SAC 305) on Immersion Tin (ImSn) surface finished after subjected to high temperature storage (HTS) at 180°C for 200 to 1000 h period. Nanoindentation approach was used to measure the micromechanical properties of the solder. It was observed that the indentation depth and plastic depth were increased and a clear trend of decreasing hardness as opposed to the increasing reduced modulus as the HTS time lengthened. The plasticity-asscociated properties become stronger meanwhile the elasticity-associated properties decreased with the HTS time. These findings indicate that nanoindentation approach can clearly determine the plastic and elastic deformation occurance throughout the test.